After the end - Plum, Amy (HarperTeen, an imprint of HarperCollins Publishers, 2015)
Seventeen-year-old Juneau is living in the Alaskan wilderness with other members of her clan, survivors of a world ravaged by World War III, but when she returns from a hunting trip one day to find her entire clan missing, she soon learns the truth that the rest of the world was never destroyed and she must navigate her way through the modern world to discover what happened to her family and friends.